Efektivitas Terapi Bermain Menggambar terhadap Kecemasan Anak Usia Sekolah 6-12 Tahun di Ruang Perawatan Anak Rumah Sakit Umum Daerah Konawe - Anisa Purnamasari; Amzal Mortin Andas; Ashar Prima; Desrinah Harahap (Jurnal Surya Medika (JSM), 2022)
The reactions shown by children undergoing hospitalization or hospitalization are generally not cooperative during treatment. Drawing play therapy is an alternative that can be used in play therapy to increase stimulation and reduce anxiety due to hospitalization during hospitalization. This study aimed to determine the effectiveness of drawing play therapy on the anxiety of school-aged children 6-12 years in the pediatric care room at the Konawe General Hospital. This type of research is a quasi-experimental design with a nonequivalent control group pre-test and post-test design. The sample in this study was 68 respondents, with a consecutive sampling technique. The method of analysis used a statistical paired sample t-test. The results showed that the results of the pre-test anxiety in the experimental group showed a mean = of 21.55 and a post-test mean = of 10.09 with a t value = 13,247. In contrast, the control group means = 22.00 and the post-test mean = 22.00 with a t value = 0.423, so the experimental group's Positive value decreases children's anxiety after the intervention. While the p-value of pre-test and post-test in the experimental group is 0.000 and the control group is 0.676, where the value is significant (0.000 <0.05), then H0 is rejected, meaning that in the experimental group, Drawing Play Therapy is effective in reducing the anxiety of school-aged children 6- 12 years old.